Application of Majapahit Architectural Elements in the Design of the Prapanca Secondary Market in Mojokerto, Jawa Timur - Wijaya, Anthony Andrey; ., Widiastuti; Mudra, I Ketut (Journal of A Sustainable Global South; Vol 2 No 2 (2018): August 2018DO - 10.24843/jsgs.2018.v02.i02.p04, 2018)
The city of Mojokerto still has buildings that use elements of its local architecture. In the city which is also called the c ity of Majapahit, historical heritage influences contemporary architecture. Many public and commercial facility buildings use local elements, both in the appearance of buildings, zoning, and ornaments. The aim is to provide identity to the building. One of the efforts of the city government that has not yet been compiled is to rearrange the area or building area in terms of its revitalization. One of them is the Prapanca Market or also called the Flea Market. Commodities offered by this mar- ket are used goods that are not suitable to be returned to the market as a whole. The purpose of this design is to in- crease the vitality of this market through the use of local elements in the appearance of buildings. Revitalization is done by developing functions, zoning, and facilities. Local architectural elements are applied to the roof and body of the build- ing, as well as the entrance. Index Terms — revitalization, local architecture, building facades, markets, mojokerto.